La reparación integral del daño a las vìctimas de violación sexual: Distrito judicial de La Libertad - Gonzales Cabanillas, Lesli Roxana (2019)
The present work has as the principal aim to determinate if the penal judges of the judicial district of La Libertad establish in their sentences the comprehensive reparation for the victims of the crime of rape through the application of conventionality control of the jurisprudential criteria establishes by The Inter-American Court of Human Rights. In order to do that, we have analyzed sentences about the crime of rape who had been issued by the magistrates of the Superior Court of Justice of La Libertad from 2010 to 2016, achieving evidence that in the extreme of reparation they only establish of penal code, as an indemnified amount, encompassing only the ambit of civil reparation regulated in the article 93 of penal code and developed in the plenary agreement N. º 6-2006/CJ-116 The final report of the investigation is divided in five parts. The first one is responsible for addressing the research plan that contains the problematic reality, background, justification, problem, hypothesis, objectives; as well as, the methodology used. The second part develops the theoretical framework that has nine chapters, which develop the social context and legal regulation of the crime of rape, the damage suffered by the victim, the criminal legal treatment of the crime victim, the reparation of the victims in the criminal process, the reparation for the victims of the crime of rape, the comprehensive reparation of the damage in the jurisprudence of the Inter-American Court of Human Rights, the comprehensive reparation of the damage to the victims of rape in the jurisprudence of Inter-American Court of Human Rights and Comparative Legislation, Conventional Control of the Inter-American Court of Human Rights Case Law and its Application in Peru, Analysis of the Judgments issued by the Criminal Judges of the Superior Court of Justice of La Libertad the years 2010 - 2016, regarding the crime of rape. Based on the above mentioned, the third part presents the results and their discussion. In the fourth part, a practical case is analyzed; and finally, in the fifth part the conclusions are shown, and the recommendations are sketched, among which a legislative proposal to modify the article 95 of the criminal procedure code, as well as, a proposal of binding jurisprudence that could be issued by the Supreme Court or Constitutional Court.